Stress release-induced interfacial twin boundary ω phase formation in a β type Ti-based single crystal displaying stress-induced α" martensitic transformation. (1st May 2018) - Yang, Y.; Castany, P.; Bertrand, E.; Cornen, M.; Lin, J.X.; Gloriant, T.
Abstract: The ω phase transformation in numerous group IV transition metals plays a key role to change the phase stability and modify mechanical properties, although its formation mechanisms and effect to accommodate strains are still unclear. A <1 1 0>β single crystal of β-type Ti-24Nb-4Zr-8Sn alloy (wt. %) is used to investigate the aforementioned problems. This alloy displays a β to α" stress-induced martensitic transformation, which is reversible and leads to superelasticity. Profiles obtained from in situ synchrotron X-ray diffraction during cyclic tensile tests reveal definitely the appearance of ω phase due to applied stress releasing after unloading while these identified ω peaks shall vanish totally on subsequent loading. TEM microstructural observations show its morphology as thin layer locating on the boundary of 1 1 2<1 1 1>β twins coinciding well with the feature of interfacial twin boundary (ITB) ω phase, which is proved to be formed passively during the reversion of 1 1 0<1 1 0>α" twins. The martensitic twinning components of 1 1 0<1 1 0>α" are indeed confirmed from crystallographic reconstructions based on the orientation relationship between the β and α" phases. A geometrical model is hence schematically used to analyze in details the orientation relationships between both deformation 1 1 2<1 1 1>β twins and ITB-ω phase, as well as with the original 1 1 0<1 1 0>α" twinning. Graphical abstract: Image 1